2014
DOI: 10.1590/0031-1049.2014.54.16
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation in the atlantic genus Siderastrea (Anthozoa, Scleractinia)

Abstract: Siderastrea is a small genus of scleractinian corals, composed by zooxanthellate massive colonial forms. Besides contributing to the consolidation of the reef structure, represent a group with significant resistance to environmental stress. Until the 70's, its taxonomy was a complicated task, limited by the difficulty in identifying morphotypes. More recently, interspecific boundaries were redefined for 'Atlantic Siderastrea Complex'. However, despite new perspectives, including the occurrence of S. radians an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Three species of Siderastrea occur in the Atlantic (Siderastrea siderea, Siderastrea stellata, and Siderastrea radians) and constitute the "Atlantic Siderastrea complex" (Menezes et al, 2014). Siderastrea stellata was believed to be endemic to Brazil but was recently found in the Gulf of Mexico (Leão and Kikuchi, 2005;García et al, 2017).…”
Section: Selection Of Species and Occurrence Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Three species of Siderastrea occur in the Atlantic (Siderastrea siderea, Siderastrea stellata, and Siderastrea radians) and constitute the "Atlantic Siderastrea complex" (Menezes et al, 2014). Siderastrea stellata was believed to be endemic to Brazil but was recently found in the Gulf of Mexico (Leão and Kikuchi, 2005;García et al, 2017).…”
Section: Selection Of Species and Occurrence Datamentioning
confidence: 99%
“…Siderastrea stellata was believed to be endemic to Brazil but was recently found in the Gulf of Mexico (Leão and Kikuchi, 2005;García et al, 2017). On the Brazilian coast, S. radians occurs simultaneously with S. stellata, and are hard to distinguish in the field due to their similar morphology (Menezes et al, 2014). Thus, considering the coinciding environmental requirements shared by these two species, we decided to model S. stellata and S. radians as a single entity (hereafter, Siderastrea sp.…”
Section: Selection Of Species and Occurrence Datamentioning
confidence: 99%
“…A single-factor MANOVA test failed to demonstrate a significant difference among the siderastreid species with respect to all skeletal traits examined (F 3,17 = 2.2937, p = 0.1146). Other morphometric studies of Siderastrea species have demonstrated similar variation in these traits (e.g., Menezes et al 2014). Skeletal (Glynn 1974) d Sessile?…”
Section: Resultsmentioning
confidence: 58%
“…Sedimentation and turbidity affect benthic assemblages (Dutra et al , 2006; Castro et al , 2012) by selecting species most well-adapted to stress and consequently reducing the percentage of coverage and diversity of taxa known to be stress-sensitive, such as scleractinian corals (Fabricius, 2005; Silva et al ., 2013). For example, S. stellata , a species endemic to the South Atlantic, has been described to have large polyps (Menezes et al ., 2014) that are less susceptible to the effect of sediments (Lirman & Manzello, 2009). Furthermore, this coral species is very resistant to temperature, salinity variations and water turbidity (Costa et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%